5-Fluorouracil Loaded Chitosan–PVA/Na+MMT Nanocomposite Films for Drug Release and Antimicrobial Activity - Reddy, A. Babul; Manjula, B.; Jayaramudu, T.; Sadiku, E. R.; Babu, P. Anand; Selvam, S. Periyar (Nano-Micro Letters, 2016)
In the present study, chitosan and polyvinyl alcohol (PVA) were blended with different concentrations of sodium montmorillonite (Na+MMT) clay solution by a solvent casting method. X-ray diffraction and transition electron microscope results show that the film properties are related to the co-existence of Na+MMT intercalation/exfoliation in the blend and the interaction between chitosan–PVA and Na+MMT. 5-Fluorouracil (5-FU) was loaded with chitosan–PVA/Na+MMT nanocomposite films for in vitro drug delivery study. The antimicrobial activity of the chitosan–PVA/Na+MMT films showed significant effect against Salmonella (Gram-negative) and Staphylococcus aureus (Gram-positive), whereas 5-FU encapsulated chitosan–PVA/Na+MMT bio-nanocomposite films did not show any inhibition against bacteria. Our results indicate that combination of a flexible and soft polymeric material with high drug loading ability of a hard inorganic porous material can produce improved control over degradation and drug release. It will be an economically viable method for preparation of advanced drug delivery vehicles and biodegradable implants or scaffolds.